2007
DOI: 10.2320/matertrans.48.531
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Heating of Thin Au Film

Abstract: Thin Au film was prepared by sputtering and evaporation methods with a quartz substrate, followed by microwave irradiation in air (frequency of microwave: 2.45 GHz, incident flux of microwave: 563 W, irradiation time: 600 s). As a result, it was confirmed that microwave heating of thin Au film is feasible. The growth of crystalline and particles due to microwave heating was confirmed from AFM observation and XRD analysis.Thin Au film is continuously heated during microwave irradiation, regardless of a preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…0.3 ..... ------------ Figure 14 shows a relationship between t..T obtained by substituting R=0.45, P=0.5, / 0 =40 nm and ~393 J/(mK) [16] into eqs. ( 7), (8) and ( 9) and L/ p in thin Cu film. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…0.3 ..... ------------ Figure 14 shows a relationship between t..T obtained by substituting R=0.45, P=0.5, / 0 =40 nm and ~393 J/(mK) [16] into eqs. ( 7), (8) and ( 9) and L/ p in thin Cu film. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of thin Cu film with a large thickness, no temperature detection appeared as shown in Figs. (5) and (8). This arises from very large Lip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another case, metallic (gold) thin films, prepared by sputtering or evaporation were, successfully heated by MW processing. The rise in temperature was a function of thickness, resistivity and microstructure of the films [37].…”
Section: Thin Films Thick Films and Tapesmentioning
confidence: 99%
“…Typically bulk metals are excellent reflectors of microwave energy and thus are not heated by microwaves. However, previous studies have showed that thin films of gold continuously absorb microwave radiation and are heated successfully [5]. This is because the microwave penetration depths (skin depth) for most metals range only a few nanometers.…”
Section: Introductionmentioning
confidence: 99%